A new genus and species of Agriotina Laporte, 1840(Coleoptera: Elateridae: Agriotini) from Colombia - Zurita-García, Martín L.; Martínez-Luque, Erick Omar; Morales-Perdomo, Jessica A.; Martínez-Duarte, Yivi D.; Noriega, Jorge Ari (Zootaxa, 2023)
Here, we describe and illustrate a new genus of Elateridae from Cundinamarca, Colombia, Raphaellus Zurita-García, Morales-Perdomo & Martínez-Luque, n. gen., to accommodate the new species R. deusminutosi Zurita-García, Morales-Perdomo & Martínez-Luque n. sp. The genus Raphaellus belongs to the subtribe Agriotina (Agriotini). A key to distinguish the genera of the New World subtribe Agriotina and taxonomic notes on Agriotini are presented.